Cortical and subcortical changes following sphenopalatine ganglion blocks in chronic migraine with medication overuse headache: a preliminary longitudinal study - Roger D. Newman-Norlund; Chris Rorden; Nasim Maleki; Milap Patel; Brian Cheng; X. Michelle Androulakis (BMC, 2020)
Abstract Objective The purpose of this pilot study was to investigate potential changes in brain morphology (cortical thickness and cortical/subcortical volume) accompanying a series of sphenopalatine ganglion (SPG) blockade treatments in chronic migraine with medication overuse headaches (CMw/MOH). Background Local anesthetization of the SPG via intranasal application is used for the treatment for multiple types of headache disorders, including CM. Our previous longitudinal fMRI study revealed improved network connectivity after such treatment. However, the impact of SPG blocks on cortical, subcortical gray matter volume and cortical thickness has yet to be assessed. Methods Using magnetic resonance imaging (MRI), cortical/subcortical volume were measured in 12 chronic migraine patients before and after a series of 12 SPG blocks administered over a 6-week period (2 per week). The average time between MRI assessments was 6 weeks. Targeted, within-subjects t-tests comparing pre-treatment and post-treatment values in specific apriori brain regions of interest, including the hippocampus, amygdala, basal ganglia, somatosensory cortex, temporal cortex and occipital cortex, were used to estimate the impact of repetitive SPG blocks treatment on brain morphology in CMw/MOH. Results Compared to baseline values, the number of moderate/severe headache days per month, HIT-6, PHQ-9 scores and allodynia scores were all significantly improved at the end of treatment. Analysis of MRI data revealed that the volume of the right hippocampus and the right palladium significantly decreased following SPG block treatment, while the volume of the left nucleus accumbens significantly increased following treatment. Cortical thickness in the left temporal pole and left lateral occipito-temporal gyrus significantly decreased following SPG block treatment. Conclusion Our results suggest SPG block treatment is associated with significant symptom improvement as well as significant structural brain changes in regions known to be associated with migraine and chronic pain processing in CMw/MOH.